Expert System Diagnosing Gastroesophageal Reflux Disease (GERD) Using Certainty-Factor Method - Riza Dwi Septa Kariza; Asep Jamaludin; Aji Perimajaya (Institute of Computer Science (IOCS), 2022)
GERD is one of the digestive system deseases that is often infected in the community, and people do not take this gastric disease seriously, this disease can cause inflammation of the throat due to stomach acid that always rises to the throat and if not treated seriously can lead to cancer. throat. The expert system in diagnosing GERD disease using the certainty-factor method is made to diagnose GERD disease early without having to go to a doctor for a diagnosis, besides this system can diagnose types of GERD disease in acute and chronic categories. This system uses the certainty-factor method because this method is suitable for measuring something that is certain or uncertain in diagnosing based on the symptoms caused. This system uses SDLC as its stage which has 5 stages including planning, analysis, design, implementation, and maintenance. besides this system is made using Mysql and PHP programming language.